Rules of fracture development in the creep of heat-resistant steels - Berezina, T.G. (Проблемы прочности, 1985)
This work is an investigation of the basic rules of the origin and development of discontinuities in heat-resistant steels under cree conditions. The materials of the investigation were steam-line pipe and specimens of 12MKh, 12KhlMF, and 15KhlMIF steels tested in a broad range of temperatures (500-650° and stresses (40-180 MPa). The study of the process of accumulation of discontinuities was made with the use of scanning and transmission electron microscopy, optical metallography, and density measurement.